Criptococosis pulmonar en una paciente con artritis reumatoide en la era COVID: reporte de caso - Valderrama-Saldaña, Mayra (2024)
Pulmonary cryptococcosis (PC) primarily affects immunosuppressed individuals, though not exclusively. The clinical presentation is variable, and reaching a diagnosis is challenging, tuberculosis and cancer being the main differential diagnoses. Due to the neurotropism of this microorganism, cerebrospinal fluid (CSF) analysis is mandatory. Treatment depends on the severity and extent of the disease, as well as the patient's immune status. We present the case of a 74-year-old patient with rheumatoid arthritis, who was being treated with prednisone, leflunomide, and methotrexate. Following a mild COVID-19 diagnosis six months prior to admission, she developed chest pain, productive cough, and progressive dyspnea. A chest CT scan revealed multiple bilateral pulmonary consolidation foci. Histological examination of tissue obtained via transthoracic percutaneous biopsy was consistent with cryptococcosis. India ink stain and cryptococcal antigen (CrAg) tests were negative in cerebrospinal fluid, while the serum CrAg was positive. Oral fluconazole was initiated, and the patient had a favorable response.